Weak localization and electron-phonon interaction in layered Zintl phase SrIn2P2 single crystal. (13th May 2021) - Wang, Huanhuan; Zhu, Xiangde; Chen, Zheng; Lu, Fangjun; Li, Huijie; Han, Yuyan; Li, Liang; Gao, Wenshuai; Ning, Wei; Tian, Mingliang
Abstract: Recently, the Zintl phase SrIn2 P2 single crystal was proposed to be a topological insulator candidate under lattice strain. Here, we report systematic electrical transport studies on the unstrained layered SrIn2 P2 single crystals. The resistance presents a minimum value around T c = 136 K and then increases remarkably at low temperature. Distinct negative magnetoresistance below T c, combined with the anomalous resistance, implies the carriers are weak localized at low temperature due to strong quantum coherence. Further analysis based on three-dimensional weak localization (WL) model suggests that the electron-phonon interaction dominates the phase decoherence process. Moreover, Hall measurements indicate that the transport properties are mainly dominated by hole-type carriers, and the WL effect is obviously affected by the carrier transport. These findings not only provide us a promising platform for the fundamental physical research but also open up a new route for exploring the potential electronic applications.